ISOLASI DAN KARAKTERISASI BAKTERI PENDEGRADASI DIAZINON DARI TANAH SAWAH DI KABUPATEN BREBES - Jebria Kwartaning Tyas; Agung Suprihadi; Budi Raharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2012)
An intensification in agriculture often faces some threats due to the existance of plant interrupted organism which often causes the decreasing of the harvest or even the failure of the harvest. The growth controlling of the Plant Interrupted Organism by using pesticide by most of the farmers has been considered as a solution that can save or protect the harvest from the attack of the Plant Interrupted Organism. The objective of this research is to get isolate and bacterial characteristic which able to degrade the diazinon. The main source of the microbes are taken from the soil sample in Brebes Regency, especially in Ketanggungan District, Wanasari District, Losari District, dan Larangan District. The research was conducted by isolation and screening for isolates followed by a characterization of bacterial isolates include morphological observations and biochemical tests. Isolates that have acquired resistance test of diazinon is then performed to determine the extent of the ability of bacteria to survive, and then to measure the growth curve and the final step is to test the degradation of diazinon by using HPLC (High Performance Liquid Chromatography). The medium which were used in isolation and screening process were Mineral Salt Medium (MSM) that had been added with diazinon 0,5 ppm and the final results obtained six isolates, there were JKB1, JKB2, JKB3, JKB4, JKB5 and JKB6. The result of resistance test showed that concentration of 90 ppm was the resistance limit of the six isolates, and the most resistance isolate was JKB3 which was shown with the greatest amount of the cells than other isolates. The growth curve was made by inoculating the isolates on MSM medium with 90 ppm diazinon, then it would get JKB5 isolate which has the highest adaptive ability. Diazinon degradation test was detected with HPLC in some varieties of incubation time, like 24, 24, and 72 hours. From this test we could get the JKB2 isolate and JKB1 isolate which had higher degradation ability than four isolates, due to a decrease in the concentration of diazinon on JKB2 at 76.27 ppm or 84.74%, followed by JKB1 70,05 ppm or 77.83%.